Chlorogenic acid inhibits cholestatic liver injury induced by α‐naphthylisothiocyanate: involvement of STAT3 and NFκB signalling regulation. (1st July 2016) - Tan, Zhen; Luo, Min; Yang, Julin; Cheng, Yuqing; Huang, Jing; Lu, Caide; Song, Danjun; Ye, Meiling; Dai, Manyun; Gonzalez, Frank J.; Liu, Aiming; Guo, Bin
Abstract: Objectives: Chlorogenic acid (CGA) is one of the most widely consumed polyphenols in diets and is recognized to be a natural hepatoprotective agent. Here, we evaluated the protective effect and the potential mechanism of CGA against ɑ‐naphthylisothiocyanate (ANIT)‐induced cholestasis and liver injury. Methods: Twenty‐five male 129/Sv mice were administered with CGA, and ANIT challenge was performed at 75 mg/kg on the 4th day. Blood was collected and subjected to biochemical analysis; the liver tissues were examined using histopathological analysis and signalling pathways. Key findings: Chlorogenic acid almost totally attenuated the ANIT‐induced liver damage and cholestasis, compared with the ANIT group. Dose of 50 mg/kg of CGA significantly prevented ANIT‐induced changes in serum levels of alanine aminotransferase, alkaline phosphatases, total bile acid, direct bilirubin, indirect bilirubin (5.3‐, 6.3‐, 18.8‐, 158‐, 41.4‐fold, P<0.001) and aspartate aminotransferase (4.6‐fold, P<0.01). Expressions of the altered bile acid metabolism and transport‐related genes were normalized by cotreatment with CGA. The expressions of interleukin 6, tumour necrosis factor‐α and suppressor of cytokine signalling 3 were found to be significantly decreased (1.2‐fold, ns; 11.0‐fold, P<0.01; 4.4‐fold, P<0.05) in the CGA/ANIT group. Western blot revealed that CGA inhibited the activation and expression of signal transducer and activator of transcription 3 and NFκB. Conclusions: These data suggest that CGA inhibits both ANIT‐induced intrahepatic cholestasis and the liver injury. This protective effect involves down‐regulation of STAT3 and NFκB signalling.